Proyecto de inversión para la implementación de un centro de servicio automotriz en el canton Daule - Fajardo Campaña, Irene Michelle (2010)
The Automotive Industry in Daule is not fully exploited, and if we further consider the fact that now the Canton and surrounding areas have a considerable number of vehicles and passenger transport units that require a quality service that will provide profitable, it has become a great opportunity to come and meet the needs of all the unsatisfied demand, the main objective of this work. The implementation of this project is a “Tecnicentro” located at Km 45 via Daule, the same as with appropriate technology and trained personnel provide services alignment, tire balancing and Sales, oil and lubricants also offer the service of Filling tires with Nitrogen gas that can be used in any type of tires and get longer life for the tires, fuel efficiency, better handling of the vehicle, getting a greater road safety.